Dark nights, bright lights : night, darkness and illumination in literature - Bach, Susanne, 1963-; Degenring, Folkert (Buchreihe der Anglia, 2015)
Night and day, light and darkness, shape our world: light signifies life, knowledge and all that is good, while darkness suggests death, ignorance and evil. And yet the darkness of the night allows not only nightmares but also dreams, it allows transformations unthinkable in the light of day. The present volume examines the interconnections of night and illumination across a broad range of literary texts.